THE INFLUENCE OF EMPLOYEE INVOLVEMENT AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH SATISFACTION AS A MODERATION VARIABLE (STUDY OF EMPLOYEE BSI KCP JAKARTA) - Adhy Firdaus (I-Economics: A Research Journal on Islamic Economics)
Abstract